Origins of bond and spin order in rare-earth nickelate bulk and heterostructures - Lu, Yi; Haverkort, Maurits W. (Physical review, 2017)
We analyze the charge- and spin-response functions of rare-earth nickelates RNiO3 and their heterostructures using random-phase approximation in a two-band Hubbard model. The interorbital charge fluctuation is found to be the driving mechanism for the rock-salt-type bond order in bulk RNiO3, and good agreement of the ordering temperature with experimental values is achieved for all RNiO3 using realistic crystal structures and interaction parameters. We further show that magnetic ordering in bulk is not driven by the spin fluctuation and should be instead explained as ordering of localized moments. This picture changes for low-dimensional heterostructures, where the charge fluctuation is suppressed and overtaken by the enhanced spin instability, which results in a spin-density-wave ground state observed in recent experiments. Predictions for spectroscopy allow for further experimental testing of our claims.
Gesehen am 07.11.2017